Climate Services for Resilient Development in South Asia Annual Report: January to December 2019 - Krupnik, Timothy J.; Hussain, Ghulam; Montes, Carlo; Schulthess, Christoph; Siddiquee, Ansar Ahammed; Rahman, Syed; Khan, Mohammad Shahidul Haque; Khanam, Fahmida; Miah, Azahar Ali; Hasan, Alfi; Kamal, Mustafa; Hossain, Khaled; et al. (2020)
Climate Services for Resilient Development (CSRD) is a global partnership that connects climate science, data streams, decision support tools, and training to decision-makers in developing countries. CSRD addresses the climate challenges faced by smallholder farmers in South Asia. The partnership is led by the United States Government and supported by the UK Government Department for International Development (DFID), the UK Meteorological Office, ESRI, Google, the Inter-American Development Bank, the Asian Development Bank, and the American Red Cross. The CSRD in South Asia initiative3 ran from November 2016 to December 2019 and was led by the International Maize and Wheat Improvement Center (CIMMYT) and funded by USAID. The consortium worked to increase resilience to climate change in South Asia by creating and making available timely and useful climate data, information, tools and services. These activities aligned with the Global Framework for Climate Services and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). In South Asia, the CSRD consortium focused primarily on Bangladesh (in alignment with Objective 1 as described above), with a secondary emphasis on Nepal and India (supporting Objective 2), and overall capacity development and awareness raising efforts across countries (Objective 3). To improve the usefulness and agricultural relevance of climate information and weather forecasts, the consortium developed strong science partnerships, and moved research into action and impact. The overarching goal was to develop and sustain the capacity development of agricultural climate services in the region. Throughout its duration, the consortium benefited from valuable inputs and guidance from USAID and its multi-partner CSRD Steering Committee.